Continuing Medical Education Questions: May 2022. (May 2022) - Inamdar, Sumant
Abstract : Article Title: Evolutionary medicine perspectives: Helicobacter pylori lactose intolerance, and three hypotheses for functional and inflammatory gastrointestinal and hepatobiliary disorders